Improving Learning Outcomes n Science Learning by Applying the Problem Based Learning Model using Power Point Media for Students in Elementary School - Alhafidz Riandeni (Cahaya Ilmu Cendekia Publisher, 2026)
Research Objective: This study aims to improve student learning outcomes in science learning with the Application of Problem Based Learning Model using power point media in class VI B at Public Elementary School 2 Way Lima. Methodology: the classroom action research conducted consists of pre-cycle, cycle 1 and cycle ii, each improvement cycle includes the planning, implementation, evaluation and reflection stages. The subjects of this study were taken from class VI B students at Public Elementary School 2 Way Lima totaling 20 students. The data collection technique was a test. Findings: Based on the research data, it shows that the application of the Problem Based Learning model using power point media can improve the learning outcomes of class VI B students at Public Elementary School 2 Way Lima. This can be shown by the completeness of learning outcomes in the pre-cycle 25%, cycle I 70% and cycle II 85%. Novelty/Originality of this study: The novelty of this research is combining the Problem-Based Learning (PBL) approach with PowerPoint presentation media as an innovation in improving student learning outcomes in science learning.